RIMA DALAM LIRIK LAGU SILAMPUKAU ALBUM DOSA KOTA DAN KENANGAN KARYA KHARIS JUNANDHARU DAN EKI TRESNOWENING (ANALISIS STRUKTURAL) - Sujoko Sujoko; Herwin Widayati (Universitas Batanghari, 2021)
This research aims to describe the rhymes in the lyrics of the song Silampukau album Dosa Kota dan Kenangan by Kharis Junandharu and Eki Tresnowening. This song by Silampukau was chosen because the lyrics have a unique building element, namely, rhyme. The method used is the descriptive method of analysis through the structural approach. This study illustrates that seven types of rhymes in the lyrics of the song, namely, the initial rhyme includes the title of the song, Balada Harian, such as Tik Tok jam dering alarm/ Tik Tok jam dering alarm. The middle rhyme includes in the title of the song Bola Raya like kami hanya main bola/ kami hanya main bola. The final rhyme includes in the title of the song Malam Di Surabaya such as ganas/ beringas. The even rhyme covers on the title of the song Bola Raya such as, Akta/ lainnya/ bola/ dakwa. The intermittent rhyme includes on the song, Balada Harian such as Alarm/ terhindarkan/ alarm/ perlahan. The compund rhyme includes on the title of the song Bola Raya such as, hijau/ terjangkau/ gedung/ buntung and the folded rhyme includes in the title of the song Sang Juragan such as, datang/ terpinggirkan/ minuman/ datang